Archives of Lithuanian Latvian Families: the Case of the Dundurnieki Starkus - Vasiliauskas, Ernestas (Acta humanitarica academiae Saulensis, 2023)
The article presents the Starkus (Latvian: Starks) family of farmers from the Daunorava (Latvian: Dundurmuiža, German: Donnerhof) Latvian dundurnieki community in Bertaučiai Village, Joniškis Parish, and the research sources on the subject matter. The research covers the following issues: (1) the 18th–19th century sources of family origin in memory preservation institutions, problem of the family origin and genealogy, the most well-known members of the family; (2) farms and sources of community demographics; (3) egodocuments and their specific features (photography collection, memoirs, diaries and letters) reflecting the economic, cultural, and social life of the community, reminiscences and genealogy of the family, kinship, and everyday activities. The sources used for the research are divided into the following categories: (1) documents in memory preservation institutions (documents of Daunorava Manor in the Latvian State Historical Archive, the Lithuanian State Historical Archives, and the Lithuanian State Central Archives: manor inventories from 1779–1797; census of souls from 1795–1834; farm censuses of 1846 and 1860; other documents from the first half of the 20th century); (2) egodocuments (1941–2007) of the Starkus Family: memoirs of the three generations of women – mother, daughter and granddaughter-niece; letters from Siberia (1948–1950); diaries of the secret agent, son-in-law Voldemaras Briedis (Voldemārs Briedis, 1944–1949); photographs from personal albums (from beginning of the 20th century to the 1970s, 285 pieces), with all digital copies stored in Aušros Museum in Šiauliai. The analysis of the Starkus case enables addressing the issue of the origin of the Latvian community of Daunorava. The community began to dominate in the area in the 18th century after massive arrival of people from Rindzele and Lēne Manors owned by German barons von der Brüggen and, possibly, from Rideļi and Balklāvi Manors owned by their relatives von Hohenastenberg gen. Wigandt in the Duchy of Courland and Semigallia. The movement most probably occurred after the plague outbreak in 1709–1710 amid the Great Northern War, when new inhabitants settled or were resettled into the considerably depopulated countryside. The question of origin may also be partly answered by means of the genealogical method, which reveals that, in the mid-18th century, most of the dundurnieki families (the Starkus, the Kaseliūnas (Latvian: Kaseļūns), the Bulis (Latvian: Bullis), the Krūminis (Latvian: Krūmiņš), the Užtupiai (Latvian: Užtupis)) had a single ancestor. The question that remains to be answered is whether a single, but well-documented case of one family can reflect the life of the community as a whole. Although comprehensive reminiscences about individual communities are lacking, several well-documented family stories can also give insight into the micro-history of the entire dundurnieki community and identify methodological access to and problems with this type of research.